Cleavage by Formamide of Intercapsomer Bonds in Adenovirus Types 4 and 7 Virions and Hemagglutinins - Neurath, A. Robert (1968)
When crude preparations of adenovirus types 4 and 7 were treated with solutions of formamide, a complete or nearly complete inactivation of infectivity could be achieved without affecting the complement fixation titers of the same preparations. Studies on purified virions showed that the intersubunit bonds within the viral capsid were broken and single capsomers were released as the result of treatment by formamide. When subjected to the same treatment, hemagglutinins were sequentially converted into incomplete hemagglutinins (pentons), which were in turn converted into penton bases and fibers.